Maternal supplementation with corn oil associated or not with di-n-butyl phthalate increases circulating estradiol levels of gerbil offspring and impairs sperm reserve - Negrin, Ana Carolina; de Jesus, Mariana Marcielo; Christante, Caroline Maria; da Silva, Danilo Grünig Humberto [UNESP]; Taboga, Sebastião Roberto [UNESP]; Pinto-Fochi, Maria Etelvina [UNESP]; Góes, Rejane Maira [UNESP] (Elsevier, 2018)
This study evaluated the consequences of gestational exposure to di-n-butyl phthalate (DBP) for testicular steroidogenesis and sperm parameters of the adult gerbil and the interference of corn oil (co), a vehicle widely used for administration of liposoluble agents, on DBP effects. Pregnant gerbils received no treatment or were treated from gestational day 8 to 23 via gavage with 0.1 mL/day of co only or containing DBP (100 mg/kg/day). Maternal co intake enhanced serum estradiol levels and testicular content of ERα and reduced sperm reserve of adult offspring. Gestational DBP exposure caused dyslipidemia, increased serum and intratesticular estradiol levels and reduced sperm reserve and motility. Thus, maternal co supplementation alters circulating estradiol and impairs sperm quantity and quality of offspring. Gestational DBP exposure alters lipid metabolism and testicular steroidogenesis and worsens the negative effects of co on the sperm reserve and motility of gerbil. Therefore, co interferes with the reproductive response to DBP.
Keywords: Corn oil; Di-n-butyl phthalate; Lipid metabolism; Sperm motility; Sperm reserve